Comparative Studies on Wine Grapes on Different Trellising Systems: II. Micro-climatic Studies, Grape Composition and Wine Quality - Van Zyl, J. L.; van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
In a field experiment the micro-climate and grape composition of four trellising systems viz., (a) Bush vines, ( b) Perold system, (c) Lengthened Perold, and (d) Slanting trellis were investigated and compared. Significantly more air movement, higher bunch and ambient air temperature as well as higher soil temperatures at 200 mm depth were recorded in the bush vines compared to the lengthened Perold and slanting trellis. Bunch temperature differences among trellising systems became most pronounced at 12h00 to 14h00.